Field and Satellite Images-Based Investigation of Rivers Morphological Aspects - Ala Hassan Nama; Ali Sadiq Abbas; Jaafar S. Maatooq (Civil Engineering Journal, 2022)
Worldwide and especially in less developed regions, process-based evaluations and/or geomorphological information on large-scale rivers are still scarce. Such investigation become of ‎urgent ‎need due to the climate change and expected occurrence of extreme floods and drought which ‎may ‎threaten the safety of nearby and downstream cities, especially in regions that are highly sensitive and ‎affected by climatic changes. The Tigris River, in Iraq, is one such river that has undergone significant alteration to its flow and morphologic aspects due to climate change and the construction of many dams. However, morphology and its change for many reaches of this river are still uninvestigated. To this end, field and satellite-based investigations into the morphology of a reach located between Makhool District and Tikrit City have been conducted. In addition to the cross-sectional survey-based determination of the reach geometrical aspects, a sinuosity indices-based evaluation of the reach planform was implemented, utilizing a satellite indices-based approach. Furthermore, the characteristics of bed material were identified through field sampling. Investigation results show that the reach has a steep bed slope and many islands of low altitude with an elongated shape. The reach has a mild sinuosity with alternating bars. The dominant particle sizes of the bed material are coarse and medium gravel with a dominant particle shape of disc particles. Moreover, the satellite-based change detection indicated the fading out and disappearance of some secondary channels, the growth of many islands, and the movement of some bends downstream. The percentage of changing parts for the period 1975–2021 is 14%. Most of this change, 11%, occurred after the construction of the Mosul Dam. This reveals the sensitivity of reach morphology to flow change due to the construction of dams. The conducted fieldwork and the applied methodology contribute to supporting efforts to add knowledge worldwide about uninvestigated rivers. Doi: 10.28991/CEJ-2022-08-07-03 Full Text: PDF